Assessment of acoustical environment condition at urban landscape. (March 2020) - Lee, Hsiao Mun; Liu, Yi; Lee, Heow Pueh
Abstract: Acoustical environment conditions of two famous landscapes at Suzhou, China were investigated. The studies were conducted through sound level measurements and questionnaire surveys at different zones at Guanqian area and Pingjiang Ancient Town. Measurement data showed that the sound levels at these two areas were considered safe for human because the maximum sound level measured from these areas was 80 dBA which was still under the permissible exposure limit (90 dBA) that recommended by Occupational Safety and Health Administration (OSHA). Negative linear relationship was found to be existed between the perceptions of quietness/comfort level and sound level at Pingjiang Ancient Town. The major sound sources at Guanqian area and Pingjiang Ancient Town were daily living and natural sounds, respectively. It was found that gender did not had significant effect on the perceptions of quietness and comfort level. It was also found that natural sound could let human felt more pleasant while machinery sound let human felt uncomfortable.